Keywords and concepts in evolutionary developmental biology - Hall, Brian K. (Brian Keith), 1941-; Olson, Wendy M., 1969- (Harvard University Press reference library., 2003)
The new field of evolutionary developmental biology is one of the most exciting areas of contemporary biology. The fundamental principle of evolutionary developmental biology ("evo-devo") is that evolution acts through inherited changes in the development of the organism. "Evo-devo" is not merely a fusion of the fields of developmental and evolutionary biology, the grafting of a developmental perspective onto evolutionary biology, or the incorporation of an evolutionary perspective into developmental biology. Evo-devo strives for a unification of genomic, developmental, organismal, population, and natural selection approaches to evolutionary change. It draws from development, evolution, paleontology, ecology, and molecular and systematic biology, but has its own set of questions, approaches, and methods.